Answer:
c
Step-by-step explanation:
if I understand this right, then the expression is
2×sqrt(28) - 5×sqrt(63)
let's look for squared factors in the numbers under the square roots.
28 = 4×7 (4 is a squared number)
63 = 9×7 (9 is a squared number)
so,
2×sqrt(4×7) - 5×sqrt(9×7) =
= 2×2×sqrt(7) - 5×3×sqrt(7) = 4×sqrt(7) - 15×sqrt(7) =
= (4 - 15)×sqrt(7) = -11×sqrt(7)
Answer:
C. 7:6
Step-by-step explanation:
Take your ratio 42 (G): 36 (B) and divide both numbers by six. This comes out to 7 (G): 6 (B) which is the simplest form of this ratio.
The first thing we must do is subtract both speeds.
We have then:
64.4 km / h - 64.0 km / h = 0.40 km / h
We now change units taking into account the following conversions:
1h = 3600s
1km = 3280.84 feets
We have then:
0.40 * (3280.84 / 3600) = 0.364537778 feet / s
Answer:
a zebra is faster 0.364537778 in feet per second
6*6=36.....................
Answer: mhm Maybe import a photo because I don’t get u
Step-by-step explanation: